2002
DOI: 10.1177/0011128702048002007
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Women's Crime and Mothers in Prison: A Peacemaking Approach

Abstract: In this article, the work of Richard Quinney and his peacemaking approach to the study of crime is used to examine the circumstances of women's crime and the effect of incarceration on women and children. Quinney's attention to events prior to the act of crime is applied to women's crime. The common life experience of prior physical or sexual abuse is among the most consistent recurring themes among incarcerated women. For these women, crime is a symptom of other painful life experiences. Quinney's peacemaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 2 publications
0
33
0
4
Order By: Relevance
“…One way to approach this task is to disseminate information about MCPs and their associated benefits through various media channels. For instance, some research suggests that women who participate in mother-child programs have reduced recidivism rates (Carlson, 1998;Radosh, 2002). Furthermore, a recent judicial decision related to mother-child visitation found that the cancellation of a provincial-level program violated the mothers' fundamental Charter rights (Inglis v. British Columba, 2013).…”
Section: Recommendationsmentioning
confidence: 99%
“…One way to approach this task is to disseminate information about MCPs and their associated benefits through various media channels. For instance, some research suggests that women who participate in mother-child programs have reduced recidivism rates (Carlson, 1998;Radosh, 2002). Furthermore, a recent judicial decision related to mother-child visitation found that the cancellation of a provincial-level program violated the mothers' fundamental Charter rights (Inglis v. British Columba, 2013).…”
Section: Recommendationsmentioning
confidence: 99%
“…Em que pese a unanimidade dos autores sobre as repercussões que o abuso sexual e outros tipos de violência determinem na saúde mental (Zavaschi et al, 2002;Arboleda-Flórez e Wade, 2001;Meyerson et al, 2002;Molnar et al, 2001;Conway et al, 2004;Hill et al, 2001;Sharma e Gupta, 2004;Steel et al, 2004;Peleikis et al, 2004;Queiroz, 2003;Grande et al, 2003;Kisiel e Lyons, 2001;Haj-Yahia e Tamish, 2001;Macfie et al, 2001;Ystgaard et al, 2004;Roelofs et al, 2002;Roberts et al, 2004), além da predisposição para um comportamento delinqüente (Gover e MacKenzie, 2003;Craissati et al, 2002;Radosh, 2002;Lindsay et al, 2001;Swanston et al, 2003;Sharma, 2003;White e Smith, 2004), seja em idade adulta (Aylwin et al, 2003) ou na juventude, não há consenso a respeito da idéia de que a criança vítima de violência será um adulto violento, capaz de práticas abusivas (Craissati et al, 2002). O abuso sexual na infância é considerado também como fator de risco para a vitimização na idade adulta (Messman-Moore e Brown, 2004; Surrat et al, 2004;Polanczyk et al, 2003).…”
Section: Discussionunclassified
“…O segundo, aos crimes da esfera sexual, enquanto o abuso físico vem sendo ligado a outros tipos de violência (Radosh, 2002;Lindsay et al, 2001).…”
Section: Revisão Da Literaturaunclassified
“…Incarceration often disrupts social bonding, which is the vital mechanism responsible for desistance from crime (Bernstein 2005;Sampson and Laub 2005). Visitation plays a key role in the maintenance of family ties, particularly for females (Radosh 2004).…”
Section: Visitorsmentioning
confidence: 99%